Pengaruh Multinationality, Tax Haven dan Tunneling Incentive terhadap Tax Avoidance Dengan Transfer Pricing Sebagai Variabel Mediasi - Serly Diva Mei; Rida Ristiyana; Isrial (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study aims to examine the influence of Multinationality, Tax Haven and Tunneling Incentive on Tax Avoidance with Transfer Pricing as a Mediation Variable. This study uses a quantitative approach with secondary data through the company's financial statements. The research population is multinational companies in the non-financial sector listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The sampling technique uses purposive sampling with a sample of 28 companies. The data analysis method uses panel data regression. The results of the simultaneous study Multinationality, Tax Haven and Tunneling Incentive have an effect on Tax Avoidance. The results of the partial study showed that Multinationality and Tunneling Incentive had a positive and significant effect on Transfer Pricing, Tunneling Incentive had a positive and significant effect on Tax Avoidance and Transfer Pricing had a negative and significant effect on Tax Avoidance. On the other hand, Tax Haven has no effect on Transfer Pricing, Multinationality and Tax Haven has no effect on Tax Avoidance. The results of the mediation effect test show that Transfer Pricing cannot mediate the influence of Multinationality, Tax haven and Tunneling Incentive on Tax Avoidance.